MDia1 senses both force and torque during F-actin filament polymerization. Issue 1 (December 2017) - Yu, Miao; Yuan, Xin; Lu, Chen; Le, Shimin; Kawamura, Ryo; Efremov, Artem; Zhao, Zhihai; Kozlov, Michael; Sheetz, Michael; Bershadsky, Alexander; Yan, Jie
Abstract Formins, an important family of force-bearing actin-polymerizing factors, function as homodimers that bind with the barbed end of actin filaments through a ring-like structure assembled from dimerized FH2 domains. It has been hypothesized that force applied to formin may facilitate transition of the FH2 ring from an inhibitory closed conformation to a permissive open conformation, speeding up actin polymerization. We confirm this hypothesis for mDia1 dependent actin polymerization by stretching a single-actin filament in the absence of profilin using magnetic tweezers, and observe that increasing force from 0.5 to 10 pN can drastically speed up the actin polymerization rate. Further, we find that this force-promoted actin polymerization requires torsionally unconstrained actin filament, suggesting that mDia1 also senses torque. As actin filaments are subject to complex mechanical constraints in living cells, these results provide important insights into how formin senses these mechanical constraints and regulates actin organization accordingly. Formins are actin-polymerisation factors that are sensitive to force. Here the authors find that pulling force on an actin filament promoted faster actin polymerisation by the formin mDia1, and also found that the actin filament must be torsionally unconstrained, suggesting that mDia1 can also sense torque.